The Role of the Skin Microbiome in Pathogenesis of Atopic Dermatitis - Current State of Knowledge - Sidz, Natalia; Brzozowska, Monika; Wardal, Wiktoria; Furlepa , Natalia; Rzenno, Robert; Wojciechowska, Karolina; Matuszewska , Marcelina; Wicha, Katarzyna; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose The subject of this article is the role of the skin microbiome in the pathogenesis of atopic dermatitis - the current state of knowledge. As is known, the skin plays a key role in protecting the body and maintaining homeostasis, cooperating with the microbiome, which affects its immune functions. The purpose of this article is to provide a comprehensive review of current research on the microbiome's role in the pathogenesis of atopic dermatitis (AD). Materials and methods The presented article was developed based on a broad database of peer-reviewed scientific publications obtained from reputable sources such as PubMed, Google Scholar and literature authored by renowned researchers from both Poland and abroad. In the process of analysis and interpretation of information, only scientific publications with a high impact factor were taken into account. The analyses performed include both clinical and experimental studies, as well as systematic reviews and meta-analyses, which allowed for obtaining a comprehensive view of the current state of knowledge in this field. Description of the state of knowledge Atopic dermatitis (AD) is a chronic inflammatory disease, the pathogenesis of which is associated with disorders of the skin microbiome, leading to the dominance of pathogenic microorganisms, such as Staphylococcus aureus. Standard methods of treating atopic dermatitis (AD) often bring only short-term relief. Understanding the role of the microbiome in this disease opens the way to new, more effective therapies, such as probiotics and methods supporting the reconstruction of skin microflora, enabling a more personalized therapeutic approach. Conclusion The aim of the article is to draw attention to the role of the microbiome in atopic dermatitis (AD), which is currently one of the most common skin diseases. It affects not only children but also adults, influencing their quality of life.